Reductionist and integrative research approaches to complex water security policy challenges. (July 2016) - Zeitoun, Mark; Lankford, Bruce; Krueger, Tobias; Forsyth, Tim; Carter, Richard; Hoekstra, Arjen Y.; Taylor, Richard; Varis, Olli; Cleaver, Frances; Boelens, Rutgerd; Swatuk, Larry; Tickner, David; et al.
Highlights: Water security policy rests on research that reduces or integrates complexity. The reductive approach can be rigid, exclusive, a-contextual, and reproduce inequalities. Options from the integrative approach advanced here are more diverse, flexible, and inclusive. To be effective, the form of analysis must match the state of knowledge possessed. To be effective, the analysis must address inequity. Abstract: This article reviews and contrasts two approaches that water security researchers employ to advance understanding of the complexity of water-society policy challenges. A prevailing reductionist approach seeks to represent uncertainty through calculable risk, links national GDP tightly to hydro-climatological causes, and underplays diversity and politics in society. When adopted uncritically, this approach limits policy-makers to interventions that may reproduce inequalities, and that are too rigid to deal with future changes in society and climate. A second, more integrative, approach is found to address a range of uncertainties, explicitly recognise diversity in society and the environment, incorporate water resources that are less-easily controlled, and consider adaptive approaches to move beyond conventional supply-side prescriptions. The resultant policy recommendations are diverse, inclusive, and more likely to reach the marginalised in society, though they often encounter policy-uptake obstacles. The article concludes by defining a route towards more effective water security research and policy, which stresses analysis that matches the state of knowledge possessed, an expanded research agenda, and explicitly addresses inequities.